Exhumations of Polish Soldiers in Lithuania: History and Methods of Research - Kadikinaitė, Jovita (Archaeologia Lituana, 2024)
The article describes the search for the remains of Polish soldiers in Lithuania from 1992 to the present day, and presents how such research has evolved, and what archaeological research methodology is used. The involvement of specialists from different institutions and disciplines in such searches is discussed. Although the article deals with the search for the remains of all Polish soldiers who died in the course of the 20th century conflicts in general, it is notable that the most numerous part of them is made up of the soldiers of Armia Krajowa. The main data available for such searches is the testimonies of live witnesses, supplemented and refined by archaeological and anthropological research. The methodology of such research is still being shaped on a case-by-case basis, so it is important to review and familiarise oneself with researches that has been carried out and cases of (un)successes, as this may help to plan further, more productive research and searches for individuals from this period in the future.
Keywords: forensic archaeology; forensic anthropology; Armia Krajowa